Using EU-SILC data for cross-national analysis: strengths, problems and recommendations - Iacovou, Maria; Kaminska, Olena; Levy, Horacio (Colchester, 2012)
"The EU’s Statistics on Income and Living Conditions (EU-SILC), launched in 2003, was the first micro-level data set to provide comprehensive data on incomes and other social and economic domains over the enlarged EU. This paper draws on two programmes of research to ask how well the EU-SILC has met the objectives with which it was designed. We focus on three areas: sampling and design, household dynamics, and incomes. In each domain the EU-SILC forms a unique and useful resource, but we also find problems and shortcomings, some of which could be rectified relatively easily, for the majority of countries."